2006
DOI: 10.1007/s00439-006-0135-z
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in DNA double-strand break repair genes and risk of breast cancer: two population-based studies in USA and Poland, and meta-analyses

Abstract: The double-strand break DNA repair pathway has been implicated in breast carcinogenesis. We evaluated the association between 19 polymorphisms in seven genes in this pathway (XRCC2, XRCC3, BRCA2, ZNF350, BRIP1, XRCC4, LIG4) and breast cancer risk in two population-based studies in USA (3,368 cases and 2,880 controls) and Poland (1,995 cases and 2,296 controls). These data suggested weak associations with breast cancer risk for XRCC3 T241M and IVS7-14A>G (pooled odds ratio (95% confidence interval): 1.18 (1.04-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
135
5
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 149 publications
(149 citation statements)
references
References 25 publications
(46 reference statements)
7
135
5
2
Order By: Relevance
“…no reporting of the relevant genotype frequencies, whereas the other [18] was excluded for examining the association between other XRCC3 polymorphisms and premenopausal breast cancer risk). As a result, 19 case-control articles [2,3,5,12,[19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]] (23 case-control studies, considering that Breast Cancer Association Consortium has more than one studies included) were included in this meta-analysis; 20 case-control studies on non-Chinese subjects (19,575 cases and 21,125 controls) and three case-control studies [3,24,29] on Chinese subjects (1,216 cases and 1,112 controls). Table 1 presents in detail the results of the meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…no reporting of the relevant genotype frequencies, whereas the other [18] was excluded for examining the association between other XRCC3 polymorphisms and premenopausal breast cancer risk). As a result, 19 case-control articles [2,3,5,12,[19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]] (23 case-control studies, considering that Breast Cancer Association Consortium has more than one studies included) were included in this meta-analysis; 20 case-control studies on non-Chinese subjects (19,575 cases and 21,125 controls) and three case-control studies [3,24,29] on Chinese subjects (1,216 cases and 1,112 controls). Table 1 presents in detail the results of the meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Kuschel and colleagues noted a significant protective effect of the variant allele of XRCC3 A17893G SNP against breast cancer in a UK population (30). This was later confirmed by two population-based studies, one conducted in the United States and the other in Poland (36). This variant allele has also been reported to confer a significantly decreased susceptibility to bladder (35), invasive ovarian (21), and upper aerodigestive (37) cancers.…”
Section: Discussionmentioning
confidence: 92%
“…For example, some studies have shown the variant allele to be associated with an increased risk for bladder, breast, and lung cancers (30,35,36,40), and these results were in agreement with the results from various functional assays showing that the variant allele was associated with an increased DNA adduct level and compromised capacity to repair X-ray-induced chromosome aberrations (42,43). In contrast, other groups found a lack of association of the T241M SNP with a risk for ovarian, skin, and endometrial cancers (20,21,39).…”
Section: Discussionmentioning
confidence: 99%
“…The variant T allele has been reported to be associated with a nonstatistically significant increased risk of squamous cell carcinoma of head and neck 37 and with a reduced risk of leukaemia, 17 whereas no association has been found in meningiomas, 38 and gastric cancer. [39][40][41] Moreover, conflicting results have been published on the associations with breast cancer, 16,21,22 lung cancer, 17,19,42 malignant melanoma 20,43,44 and bladder cancer. 17,18,45 It was also noted that the frequency of the XRCC3-241Met allele in our control group (5.9%) was similar to that previously reported in a Chinese population, 39 but quite different from that found in Caucasians and African Americans, suggesting that the Met allele frequency could vary by ethnicity.…”
Section: Discussionmentioning
confidence: 99%
“…14 The currently available high density of markers in specific chromosomal regions enables us to investigate possible involvement of a number of genes in the development of complex diseases using linkage disequilibrium (LD) to associate markers with disease occurrence at the population level. To our knowledge, few molecular epidemiologic studies have been published on cancer susceptibility associated with XRCC3 haplotypes, [15][16][17][18][19][20][21][22] whose allelic combination may serve as better makers for unknown functional variants than any single nucleotide polymorphism (SNP). Still, to date, and none of studies on XRCC3 haplotypes examined glioma risk.…”
mentioning
confidence: 99%